Analysis of Worker Satisfaction with the Foreman's Leadership in Building Construction Works using Importance Performance Analysis - Harun, Mohamad; Marjono; Sugiono; Lisa Dwi Wulandari (Wacana Journal of Social and Humanity Studies, 2023)
Job satisfaction is important for workers, which can encourage them to work better. The factor that influences worker satisfaction is leadership because it can create good working relationships so that it will have an impact on performance. This study aims to analyze worker satisfaction with the foreman's leadership style in building construction work and determine what attributes need to be maintained and improved to achieve a good level of satisfaction for building construction workers. The method for analyzing worker satisfaction uses Importance Performance Analysis (IPA IPA) to determine worker satisfaction by measuring the importance and implementation level. The results showed that the respondent's conformity level was 87%, meaning the workers were satisfied with the foreman's leadership. The attributes that must be maintained to increase worker satisfaction are: (1) leaders always have good relations outside the work environment, (2) leaders are always careful in accepting and hiring workers, and (3) being consistent in what is said with what is done. The attributes that must be prioritized to increase worker satisfaction are (1) leaders always serve workers well in the work environment, (2) leaders can control themselves if there are problems and encourage positive development, (3) be consistent in what is said with what is done and (4) always paying attention to the gains and losses in work.